Mediastinal Primitive Neuroectodermal Tumour (PNET) A Rare Case of Horners Syndrome - Das, Anirban; Roy, Partha Pratim; Sarkar, Anirban; Datta, Samadarshi; Dey, Subir; Basu, Nandita (Journal of Medicine, 2012)
Primitive neuroectodermal tumour (PNET) is a rare mediastinal tumour which may infiltrate pulmonary parenchyma and chest wall. Histopathologically, it is a round cell tumour, and on immunohistochemistry, tumour cells express for CD – 99 (MIC – 2). Here we report a rare case of PNET presented as unresectable mediastinal tumour with chest wall infiltration, superior vena caval obstruction and Horner’s syndrome in an adolescent female. DOI: http://dx.doi.org/10.3329/jom.v13i1.8762 JOM 2012; 13(1): 85-87